1998
DOI: 10.1128/iai.66.6.2996-2998.1998
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Xylose, Mannose, and Mannitol for Synthesis of Glucuronoxylomannan of Cryptococcus neoformans Determined by 13 C Nuclear Magnetic Resonance Spectroscopy

Abstract: Cryptococcus neoformans NIH 409 was cultured in a defined medium containing d-[1-13C]xylose (Xyl), d-[1-13C]mannose (Man), ord-[1-13C]mannitol as the sole carbon source. The distribution of 13C in the Man, Xyl, glucuronic acid (GlcA), and O-acetyl constituents of native and de-O-acetylated glucuronoxylomannan (GXM) was determined by one-dimensional13C nuclear magnetic resonance spectroscopy. The carbon chain of Man was incorporated intact into GXM since13C was observed only in carbon 1 of Man, GlcA, and Xyl. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…To confirm that radioactivity was incorporated into GXM, we incubated the supernatants obtained after the radiation with sepharose conjugated with the mAb to GXM 18B7, and observed that most of the radioactivity was retained by the sepharose matrix (result not shown). This result indicated that most of the radioactive mannose was incorporated into GXM, a finding consistent with previous report that mannose is incorporated directly into GXM (Cherniak et al ., 1998).…”
Section: Resultssupporting
confidence: 92%
“…To confirm that radioactivity was incorporated into GXM, we incubated the supernatants obtained after the radiation with sepharose conjugated with the mAb to GXM 18B7, and observed that most of the radioactivity was retained by the sepharose matrix (result not shown). This result indicated that most of the radioactive mannose was incorporated into GXM, a finding consistent with previous report that mannose is incorporated directly into GXM (Cherniak et al ., 1998).…”
Section: Resultssupporting
confidence: 92%
“…The cryptococcal capsule is composed of two major PSs, glucuronoxylomannan (GXM) and galactoxylomannan (GalXM) (Doering, 2000;Mcfadden et al, 2007;Frases et al, 2008;Villena et al, 2008;Yoneda and Doering, 2008). GXM comprises approximately 90% of the capsule and is formed by a linear (1→3)-a-dmannopyranan main chain bearing b-d-xylopyranosyl (Xyl) in b(1→2) or b(1→4) linkages (Cherniak et al, 1998a), (1→2)b-d-glucopyranosyluronic acid (GlcA) attached to every third mannose, on average, and 6-Oacetyl substituents (Kozel et al, 1988;Cherniak et al, 1998a, Reese andDoering, 2003;Mcfadden et al, 2006a,b;Nimrichter et al, 2007;Frases et al, 2008). GalXM is an a(1→6)-galactan containing b(1, 3) oligosaccharyl substitutions at alternate residues of galactose.…”
Section: Introductionc Mi_1430 740753mentioning
confidence: 99%
“…Creatinine is not used as a source of carbon by C. neoformans , but is used as a source of nitrogen [ 81 ]. C. neoformans can use xylose, mannose, and mannitol as a sole carbon source [ 82 ]. Cherniak et al used nuclear magnetic resonance spectroscopy (NMR) to study the assimilation of radiolabelled [1-13C]Xyl, [1-13C]Man, and [1-13C]mannitol mannose and their incorporation into capsular glucuronoxylomannan (GXM) [ 82 ].…”
Section: Nutrition In the Environment And Virulence In The Hostmentioning
confidence: 99%
“…C. neoformans can use xylose, mannose, and mannitol as a sole carbon source [ 82 ]. Cherniak et al used nuclear magnetic resonance spectroscopy (NMR) to study the assimilation of radiolabelled [1-13C]Xyl, [1-13C]Man, and [1-13C]mannitol mannose and their incorporation into capsular glucuronoxylomannan (GXM) [ 82 ]. The carbon chains of both mannose and mannitol are incorporated into capsular polysaccharide whilst the carbon chain of xylose was not incorporated intact by the yeast and it was suggested that xylose is assimilated through the pentophosphate pathway (hexose monophosphate shunt).…”
Section: Nutrition In the Environment And Virulence In The Hostmentioning
confidence: 99%